2009
DOI: 10.1007/s11060-009-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ganciclovir-sensitive lentiviral vector to assess the influence of angiopoietin-3 and soluble Tie2 on glioma growth

Abstract: Malignant brain tumors grow by coopting the existing vasculature, a process involving the release of angiopoietin-2 (Angpt2) from endothelial cells and its binding to the Tie2 receptor. The first goal of this study was to examine the therapeutic potential of two proteins that could interfere with Angpt2, namely Angpt3 and the soluble extracellular domain of Tie2 (sTie2). The second goal was to develop a lentiviral vector capable of delivering such proteins while offering the possibility to identify and destroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…1b, d, f, g and l). Leptomeningeal spread in human DIPG is often detected at recurrence [44] and it was found both in h-VUMC-DIPG-5 and in m-VU-DIPG-3 and -5 (Fig. 1b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b, d, f, g and l). Leptomeningeal spread in human DIPG is often detected at recurrence [44] and it was found both in h-VUMC-DIPG-5 and in m-VU-DIPG-3 and -5 (Fig. 1b and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The glioblastoma cells often exploits the existing host vessels to grow or invade, which is vessel cooption [16,17]. Vessel cooption was a strong explanation for the invasion or metastasis of malignant brain tumors [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Vessel cooption was a strong explanation for the invasion or metastasis of malignant brain tumors [16][17][18][19][20]. The coopted vasculature initiates structural and functional change to better suit glioma growth [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overexpression of Ang-3 might inhibit tumor angiogenesis in pulmonary metastasis of Lewis lung carcinoma and TA3 mammary carcinoma cells (Xu et al, 2004). Further studies found that Ang-3 was expressed in the uterus, placent, and testes (Kim et al, '99;Matsumoto et al, 2002;Beaudet et al, 2010). However, Ang-3 expression and hormonal regulation in mouse uterus during the peri-implantation were still not defined in detail so far.…”
mentioning
confidence: 99%